Macerie, resti, residui nella poesia di Fabio Pusterla - Stroppa, Sabrina (L’ospite ingrato, 2023)
Starting from the conceptual distinction between ruin and rubble, the article investigates and categorizes the recurring forms of residuality in Fabio Pusterla’s work in verse, tracing the essential coordinates of a poetics of the residue and of a “theory of the rest”. In fact, the natural landscape, devoid of any composure or coherence in its presentation, is in solidarity with the anthropic residue, for which the waste and debris of human passage are the signals and fragments that the eye tirelessly captures and enhances, predisposing them to be inhabited by language. At the heart of Pusterla’s poetic gesture it therefore seems possible to identify a practice of language that knows how to keep the relationship with time open, and therefore with the narrative, projecting a tale of origins, with its ancestral nobility, towards a looming future.